1977
DOI: 10.1002/cpt1977216731
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of the enterohepatic circulation of phenprocoumon by cholestyramine

Abstract: The effect of cholestyramine (12 gm/day divided into 3 doses) on the pharmacokinetics and pharmacodynamics of a single intravenouse dose (30 mg) of phenprocoumon was studied in 6 normal subjects. Cholestyramine treatment led to an increase in the rate of elimination of phenprocoumon in all. Total clearance increased 1.5- to 2-fold. The total anticoagulant effect per dose was considerably reduced during treatment with cholestyramine. Binding studies in vitro showed that phenprocoumon is strongly bound to choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
1
5
0
Order By: Relevance
“…The pharmacokinetic parameters of phenprocoumon obtained in this study are similar to those which have been reported earlier following administration of single doses [5,11] and during steady-state [7]. Pharmacokinetics of phenprocoumon are characterised by low clearance (0.7−0.8 ml/min), long half-life (6−7 days) and a high degree of binding to plasma proteins (> 99 %).…”
Section: Discussionsupporting
confidence: 84%
“…The pharmacokinetic parameters of phenprocoumon obtained in this study are similar to those which have been reported earlier following administration of single doses [5,11] and during steady-state [7]. Pharmacokinetics of phenprocoumon are characterised by low clearance (0.7−0.8 ml/min), long half-life (6−7 days) and a high degree of binding to plasma proteins (> 99 %).…”
Section: Discussionsupporting
confidence: 84%
“…The marked age-dependent decrease in the clearance of phenprocoumon found in this study could be caused in part by the somewhat different metabolic pattern of phenprocoumon compared to warfarin. A greater percentage of the dose of phenprocoumon is primarily glucuronidated in the liver and is subject to an enterohepatic circulation [24]. On the other hand, the kind of underlying pathology may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…The absorptioni of racemic warfarin was not affected even by diseases associated with severe gastrointestinal malabsorption. Cholestyramine in man interfered with the absorption of racemic warfarin causing it to appear in the stool (9), and also interfered with the absorption and subsequent hypoprothrombinemic effect of racemic phenprocoumon (10). Barbiturates did not affect the absorption of racemic warfarin, but did reduce the absorption of dicumarol (11).…”
Section: Discussionmentioning
confidence: 99%